Cyphellophora sp. Isolated from a Corneal Ulcer in the Human Eye. (22nd July 2020) - Rajandran, Satheitra; Razali, Kursiah Mohd; Mustapha, Mushawiahti; Palaniappan, Prem Ananth; Amran, Fairuz
Abstract : Cyphellophora is a black yeast-like fungus with most of the strains being isolated from soil and plants. It tends to cause sooty blotch and flyspeck disease in plants. In humans, it is known to cause superficial skin and nail infections. This report highlights the case of a patient who initially presented with a small corneal abrasion which rapidly progressed into a corneal ulcer after the patient did not respond to the initial conventional treatment. The laboratory results from the corneal scraping found it to be Cyphellophora sp.